2016
DOI: 10.1038/srep30259
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological fingerprints of OFF bipolar cells in rat retina

Abstract: Retinal bipolar cells (BCs) divide photoreceptor output into different channels for the parallel extraction of temporal and chromatic stimulus properties. In rodents, five types of OFF BCs have been differentiated, based on morphological and functional criteria, but their electrophysiological characterization remains incomplete. This study analyzed OFF BCs with the patch clamp technique in acute slices of rat retina. Their specific voltage-dependent currents and glutamate responses are shown to represent indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…These are sometimes specific between particular bipolar cell and cone types (e.g., M cone and CBC1, or S cone and CBC9), and only one type of bipolar cell would connect with the rods, although there also appear to be connections between rod and cone pathways [62]. Bipolar cells respond to the release of glutamate by photoreceptors in their synaptic communication [63] and adopt a mosaic arrangement, in which the overlapping contacts are potential synaptic pairings. Connectivity can be studied using electron microscopy, molecular markers, or more recently, computational methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are sometimes specific between particular bipolar cell and cone types (e.g., M cone and CBC1, or S cone and CBC9), and only one type of bipolar cell would connect with the rods, although there also appear to be connections between rod and cone pathways [62]. Bipolar cells respond to the release of glutamate by photoreceptors in their synaptic communication [63] and adopt a mosaic arrangement, in which the overlapping contacts are potential synaptic pairings. Connectivity can be studied using electron microscopy, molecular markers, or more recently, computational methods.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies using electrophysiological analysis, Vielma and Schmachtenberg [63] reported the existence of various types of OFF bipolar cells that exhibit different responses depending on glutamate levels; specifically, bipolar cells BC 3a, 3b, and 4 exhibited a significant inhibitory input in response to glutamate and were subject to inhibitory modulation with nitric oxide (NO). They also showed 6 functionally distinguishable types of bipolar cells with combinations of individual glutamate channels and receptors that give them unique electrophysiological filtering and signal-processing properties.…”
Section: Discussionmentioning
confidence: 99%
“…S1). 29 The sIPSCs were also recorded from different subtypes of amacrine cells voltage-clamped at 0 mV with patch electrodes (7-8 MΩ) containing K + gluconate internal solution. Although AII amacrine cells were distinguished by their smaller somata, a prominent primary dendrite protruding into the IPL, and a narrowly distributed dendritic arbor, other subtypes of amacrine cells were divided according to their dendritic stratification within different portions of the IPL as ON, OFF, or ON-OFF amacrine cells.…”
Section: Methodsmentioning
confidence: 99%
“…24 In the OFF pathway, the classic view is that glycinergic inhibitory input to OFF BCs stems mainly from AII amacrine cells, a key component in signal transmission within the rod pathway. [25][26][27] However, depending on the OFF BC type 21,[28][29][30][31] and the degree of light adaptation, inhibitory input from both glycinergic and GABAergic sources contributes to the functional requirements of the retina. [32][33][34] Although little is known regarding the exact localization and function of CB1R within the OFF pathway, the dense labeling of CB1R in the inner plexiform layer (IPL), 7,9,35 the apparent localization of CB1R at the cone-type 1 OFF BC synapse, 35 in some recoverin-positive OFF BCs, 19 and in subsets of GABAergic 9 and putative glycinergic amacrine cells, 19 suggest that CB1Rs can control OFF BC function by regulating their activity and/or inhibitory input in the inner retina, but this remains currently unproven.…”
mentioning
confidence: 99%
“…In these cells, NO initially modulates the signal generally by altering the cGMP levels [126]. Thus, some studies demonstrated the involvement of NO through activation of the sGC-cGMP-PKG pathway, acting as a modulator of the temporal properties of the glutamate response [129,130]. Perfusion of acute slices of rat retina with the NO precursor L-arginine shortened the AMPA receptor-dependent component of the glutamate response and did not change the kainate receptor-dependent component in bipolar cells [129].…”
Section: No and Ampars In Retina As An Example Of Mutual Interactionmentioning
confidence: 99%